Clinical implications of left atrial reverse remodelling after cardiac resynchronization therapy. (25th February 2022) - Stassen, Jan; Galloo, Xavier; Chimed, Surenjav; Hirasawa, Kensuke; Marsan, Nina Ajmone; Delgado, Victoria; van der Bijl, Pieter; Bax, Jeroen J
Abstract: Aims: Left atrial (LA) function is a marker of prognosis in patients with heart failure. The prognostic implications of an improvement in LA function in addition to an improvement in left ventricular (LV) function after cardiac resynchronization therapy (CRT) implantation are unknown. This study aimed to evaluate the prognostic value of a significant change in LA reservoir strain (RS) and/or LV global longitudinal strain (GLS) after initiation of CRT. Methods and results: LARS and LVGLS were measured with speckle-tracking echocardiography. Significant improvement in LARS and LVGLS was defined as a percentage change of +5% and +20% at 6 months after CRT implantation, respectively. Patients were divided into three groups: no significant reverse remodelling (no improvement in LARS and LVGLS), incomplete reverse remodelling (improvement in LARS or LVGLS), and complete reverse remodelling (improvement in LARS and LVGLS). The primary endpoint was all-cause mortality. A total of 923 patients (mean age 65 ± 10 years, 77% male) were included, of which 221 (24%) had complete reverse remodelling, 414 (45%) incomplete reverse remodelling, and 288 (31%) no significant reverse remodelling. Five-years' mortality was 24%, 29%, and 36% for patients with complete, incomplete, and no significant reverse remodelling, respectively ( P < 0.001). On multivariable analysis, complete reverse remodelling (hazard ratio 0.477; 95% confidence interval: 0.362–0.628; P < 0.001) was associated with the lowest risk of mortality. Conclusions: Patients with complete reverse remodelling have a lower mortality risk than those showing incomplete or no significant reverse remodelling. The use of integrated LA and LV deformation imaging may improve risk-stratification of CRT recipients. Graphical Abstract: